Energy Eigenvalues, Dipole Polarizability, Electron Pressure and Effect of Dielectrics on the Confined Hydrogen Atom - Maibam, Rupachandra; Sharma, Ashish (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2024)
In this work, we used an efficient computational technique to solve the Schrödinger equation for the confined hydrogen atom (CHA) which is confined inside a hard spherical cavity with impenetrable wall. The wavefunctions, energy eigenvalues, polarizability and pressure have been calculated for different confinement radius. The energy eigenvalues and expectation values obtained are in good agreement with those calculated values obtained by Aquino et al. [2]. The hydrogen atoms under high pressure are real physical systems which can be found inside astrophysical objects.